SISTEM KETENAGAKERJAAN DALAM KONSTELASI HUKUM POSITIF DAN HUKUM ISLAM DI INDONESIA - Haris Djayadi (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2021)
This study aims to describe the meaning of the constellation of the labor system in the perspective of positive law and Islamic law. The labor system in Indonesia is regulated in Law no. 13 of 2003 concerning manpower. Meanwhile, labor in the study of Islamic law is explained in fiqh muamalah with the concept of ijarah or renting. The results of this study indicate that the relation of the labor system is found in the perspective of positive law and Islamic law. First, the labor system in which it describes "workers" has been regulated in positive legal regulations through the Act. Meanwhile, "workers" in the terminology of Islamic law command every human being who lives on earth to work as a form of worship to Allah SWT. Second, the labor system in Indonesia has been regulated in Law no. 13 of 2003 concerning employment, while the labor system in Islamic law is better known as ijārah, in which there are pillars and conditions that must be met. Third, the two areas of law define the same rights and obligations for workers.